A educação patrimonial como instrumento de (re)significação e estímulo ao pertencimento às cidades estigmatizadas - Liza Iole da Silva Caetano (2021)
How can the incorporation of heritage education in schools contribute to the (re) construction of cultural identity in stigmatized cities? This is the question that guides our research, which aims to develop educational strategies and materials for the (re) construction of the cultural identity of stigmatized cities. Our focus was on municipal schools in Ribeirão das Neves, but we hope that the results of this research can also serve educators from other municipalities with similar characteristics and challenges. We use the participatory inventory methodology, which seeks to encourage the community to act as a protagonist in identifying and valuing their cultural references. As a result of the research, a Heritage Education kit was developed, consisting of an accessible children's book, games and a website with versions in pounds, audio description and complementary material for the teacher. The didactic material was developed with the participation of students, through the interdisciplinary project “Rediscovering and valuing the place where I live” and with the support of the Dean of Extension of UFMG was distributed in all municipal schools in Ribeirão das Neves. The text presents reflections on Patrimonial Education and points out a way to assist in critical thinking and in the (re) construction of the cultural identity of stigmatized cities, with timely redefinition of spaces and memories. The study is based on the assumption that it is important to expand knowledge and value local heritage in municipalities that have a negative public image, as a place of violence and poverty. These factors make their own residents avoid identification and belonging. Thus, we find in Heritage Education, in conjunction with student-centered learning, the possibility of recreating new narratives and new meanings. The story is not unique and other stories must be told. This was our biggest challenge, we launched a small contribution “seed”, which requires preparation, energy, cultivation and time for germination.